An Impact of Financial Literacy on Investment Choices for Working Women in Bengaluru City, India - S. Ramesh; Umamaheswari S.; Y. Fathima (Contemporary Research in Business, Management and Economics Vol. 9, 2024)
The present study highlights about financial literacy of working women respondents and their preferred source of investments in financial products. Financial literacy is a prominent aspect of Individual growth and the economic development of a country. It is a strong pillar of the wellbeing of society and develops the standard of living of people. The growth and development of a location or people are all determined by their financial circumstances. Finance plays an important part in measuring people’s living standards and evaluating a country’s economic growth. As a result, people should be aware of the numerous sources of financial investment and their importance. In this study, financial literacy is mentioned as knowledge of various investment sources of finance like bank savings, post office savings, Investment in mutual funds, capital market and gold. Hence, the study collected information through questionnaires from different categories of working women respondents. The data was collected from respondents with the questions entailing their knowledge of various sources of financial investment and its avenues. To test the hypothesis, the research study employed One-way ANOVA and basic descriptive statistics. According to the study, the majority of women are competent with loans, savings, and borrowing, but they lack expertise in handling investment-related concerns, calculating interest rates, having minimal exposure to long-term investments, and showing little interest in routinely keeping track of their spending. The study also revealed that the attitude of women towards savings and borrowing o is statistically more significant than other factors. The study also found that in a family, women’s income has a significant and impact on the knowledge of women concerning savings–borrowings and financial investment. Though the respondents are illiterate, but they had less exposure on financial investment. It shows that most of the women required to take financial training from the organisation with their family, friends, and other welfare associations.